The Relationship Between Service Quality and Customer Loyalty in Online Shopping - Nurul Atiqah Hariyanto; Siti Aisyah Salim (Research in Management of Technology and Business, 2024)
Online shopping is the practice or action of making purchases of products or services over the internet. Online shopping activities in Malaysia become more popular due to COVID-19 and many people have increased their reliance on buying things thru online commerce and switched to it. During Movement Control Order (MCO), Shopee was the most popular e-commerce platform and followed by Lazada. But in April last year, TikTok has launched TikTok Shop in Malaysia which quickly became an effective E-Commerce solutions provider for its users as it is combining the forces of community, creativity and commers by offering a smooth purchasing experience while enabling brands and creators to reach highly engaged consumers based on their interests. The problem statement is ensuring and maintaining customer loyalty through service quality provided. This study was focused to analyse the level of service quality and customer loyalty in online shopping, to analyse the relationship between service quality and customer loyalty in online shopping. The population of this study comprises of all the 6.5 million Malaysian that using online shopping platforms e.g. Shopee, TikTok in doing online shopping. The Krejcie and Morgan table was used to determine an appropriate sample size for the study is 384 respondents. This study used the method of quantitative which is questionnaire distributed by Google Form to gather the data. This study has collected data from 215 respondents among online shopping user in Malaysia with response rate of 56%. The hypotheses were tested using the Spearman’s Correlation Coefficient with the help of Statistical Tool for Social Science (SPSS). All the hypotheses were accepted in this study. The crucial in findings the relationship between service quality and customer loyalty is achieved and the reliability, responsiveness and assurance had significant relationship with customer loyalty in online shopping.